2023
DOI: 10.1126/sciadv.adh4030
|View full text |Cite
|
Sign up to set email alerts
|

The youth mental health crisis: Quasi-experimental evidence on the role of school closures

Christina Felfe,
Judith Saurer,
Patrick Schneider
et al.

Abstract: During the COVID-19 pandemic, the youth mental health crisis has reached unprecedented levels. To which extent school closures, one of the most heavily debated pandemic measures, have contributed to or even caused this crisis is largely unknown. We seek to narrow this blind spot, by combining quasi-experimental variation in school closure and reopening strategies across the German federal states at the onset of the pandemic with nationwide, population-based survey data on youth mental health and high-frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…29 Sex differences were also suggested by a recent report that prolonged school closure in Germany was associated with more marked worsening in mental health among boys. 19 An unexpected finding was that coming from a lower socioeconomic status neighborhood was associated with an increased rate of psychiatric ED visits only among males (eTable 2 in Supplement 1). Few studies have examined sex as a possible factor in the association between socioeconomic status and child mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Sex differences were also suggested by a recent report that prolonged school closure in Germany was associated with more marked worsening in mental health among boys. 19 An unexpected finding was that coming from a lower socioeconomic status neighborhood was associated with an increased rate of psychiatric ED visits only among males (eTable 2 in Supplement 1). Few studies have examined sex as a possible factor in the association between socioeconomic status and child mental health.…”
Section: Discussionmentioning
confidence: 99%
“…5,18 Conversely, there are also suggestions that the prolonged duration of COVID-19 school closure was associated with worse adolescent mental health. 19 In Italy, the strictest COVID-19 preventive restrictions (social lockdown with limitation of in-person schooling) started in the spring of 2020 and were in force for most of that year, with gradual attenuation, based on the fluctuating incidence of the infection, in 2021. School was online in many areas, at least during some weeks, until the summer of 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic and mitigation measures aggravated social isolation, limited peer contact and play, and disrupted interpersonal school-based learning in school-going children. A growing body of literature suggests prolonged school closures impeded academic progress and contributed to "learning loss" in children [29,30]. However, there is a dearth of empirical data on the prevalence of pediatric cognitive problems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature on race and gender disparities in mental health impacts has yielded mixed findings. Some studies have found a higher prevalence of affective disorders in girls [4,6], while there is some evidence that boys fared worse in coping with school closures during COVID-19 [30]. Non-Hispanic whites have been found to have a higher prevalence of mental health problems than similarly situated blacks or other minorities [31], a finding often attributed to better coping skills or resilience levels among minorities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Dabei kommt Schule und Unterricht selbst wiederum eine zentrale Bedeutung bei der Entwicklung und Stabilisierung von psychischer Gesundheit zu: In keiner anderen Institution verbringen Kinder und Jugendliche so viel Zeit wie in Bildungseinrichtungen, kaum eine andere Institution prägt zentrale Bereiche der psychischen Entwicklung und des psychischen Wohlbefindens so sehr wie Schule. Besonders im Nachklang der COVID-19-Pandemie mit ihren erheblichen negativen Auswirkungen von Schule und Unterricht belegen wissenschaftliche Studien, dass schul-und unterrichtsassoziierte Faktoren wie Lernrückstände, provisorischer Distanzunterricht und fehlende schulische soziale Kontakte tiefe Spuren in der psychischen Gesundheit von Schüler:innen hinterlassen haben (Felfe et al, 2023). Dabei sollte aber auch beachtet werden, dass eine Flexibilisierung von Präsenz-und Distanzunterricht besonders in Familien mit guten persönlichen und materiellen Ressourcen auch positive Auswirkungen auf das Wohlbefinden von Schüler:innen hatte (Thorell et al, 2022), dies also auch einen wichtigen Ansatzpunkt der Gesundheitsförderung für bestimmte Schüler:innengruppen darstellt.…”
Section: Psychische Gesundheit Von Schüler:innen In Deutschlandunclassified